Generation of 3D Soluble Signal Gradients in Cell‐Laden Hydrogels Using Passive Diffusion. Issue 1 (14th November 2018) - Ahrens, Lucas; Tanaka, Simon; Vonwil, Daniel; Christensen, Jon; Iber, Dagmar; Shastri, V. Prasad
Abstract: Soluble signal gradients play an important role in organ patterning, cell migration, and differentiation. Currently, signal gradients in 2D cell culture are realized using microfluidics and here cells are exposed to high and nonphysiological shear stress. Tissue morphogenesis (organogenesis) however occurs in 3D and therefore there is a need for simple and practical systems to impose gradients to cells dispersed in 3D matrix. Herein, a 3D gradient generator based on passive diffusion elements that recapitulates interstitial flow and is capable of imposing predictable gradients over long length scales (6 mm) lasting up to 48 h to cells dispersed in a hydrogel environment is reported. Using recombinant human WNT3A (rhWNT3A), the spatiotemporal activation of the canonical WNT pathway in human epithelial kidney cells and human mesenchymal stems cells expressing a green fluorescence protein reporter on a transcription factor/lymphoid enhancer‐binding factor (TCF/LEF) promoter is demonstrated. By refining computation models based on experimental findings, the diffusion coefficient of rhWNT3A in presence of human cells in 3D is determined. Furthermore, the formation of rhBMP4 gradients is visualized using immunohistochemistry by staining for phospho‐SMAD1/5, the downstream targets of the bone morphogenetic protein (BMP) pathway. The simplicity of the gradient generator is expected to spur its adoption in studying developmental biology paradigms in vitro. Abstract : Organization of cells into tissues/organs involves carefully orchestrated presentation of soluble cues as a function of space and time. Using passive diffusion elements, an in vitro system wherein growth factors can be presented in a spatially and temporally defined manner is realized and the utility of this system in activating WNT and BMP signaling pathway in human cells is demonstrated.